2016
DOI: 10.1002/jor.23148
|View full text |Cite
|
Sign up to set email alerts
|

Targeting formyl peptide receptor 1 of activated macrophages to monitor inflammation of experimental osteoarthritis in rat

Abstract: Macrophages play a crucial role in the pathogenesis of osteoarthritis (OA). In this study, the feasibility of a formyl peptide receptor 1 (Fpr1)-targeting peptide probe cFLFLF-PEG- 64Cu via positron emission tomography (PET) imaging was investigated for detection of macrophage activity during development of OA. Monoiodoacetate (MIA) was intraarticularly injected into the knee joint of Sprague-Dawley rats to induce OA. Five days later, cFLFLF-PEG-64 Cu ($7,400 kBq/rat) was injected into the tail vein and microP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
(55 reference statements)
1
17
0
Order By: Relevance
“…FAM3D deficiency repressed Ly6C high monocyte recruitment and macrophage infiltration in infrarenal abdominal aortas after elastase induction. As Mac-1 also plays a critical role in monocyte recruitment, as well as FPRs are markedly expressed in monocytes/macrophages, 51 , 52 we evaluated the activation of Mac-1 in human monocytes after FAM3D treatment. Indeed, FAM3D could activate Mac-1 in monocytes as well (Figure XII in the online-only Data Supplement ).…”
Section: Discussionmentioning
confidence: 99%
“…FAM3D deficiency repressed Ly6C high monocyte recruitment and macrophage infiltration in infrarenal abdominal aortas after elastase induction. As Mac-1 also plays a critical role in monocyte recruitment, as well as FPRs are markedly expressed in monocytes/macrophages, 51 , 52 we evaluated the activation of Mac-1 in human monocytes after FAM3D treatment. Indeed, FAM3D could activate Mac-1 in monocytes as well (Figure XII in the online-only Data Supplement ).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage imaging for detection of active joint inflammation is now being investigated in both animal models [23■■] and humans [24■■]. In a small pilot study of knee osteoarthritis patients [24■■], administration of a labeled folate-receptor agonist to identify activated macrophages using SPECT/CT (single photon emission computed tomography) imaging was reported [24■■].…”
Section: Local Infiltration Of Cellsmentioning
confidence: 99%
“…76% of knees demonstrated positive signal in capsule, synovium, and subchondral bone, which correlated with radiographic and symptom severity. In a rat model, a labeled formyl peptide receptor-1 (FPRI) agonist was used for similar purposes [23■■]. Computed tomography (CT) and PET imaging 5 days after intra-articular injection of mono-iodoacetate to induce osteoarthritis showed that this agent preferentially localized to the treated knee, and confocal imaging of tissue sections confirmed localization to synovial macrophages.…”
Section: Local Infiltration Of Cellsmentioning
confidence: 99%
“…Increasing evidence supports that synovial macrophages play an important role in the progression of osteoarthritis 11 - 13 . Firstly, the accumulation of macrophages at the synovial lining and cartilage surfaces is the first symptom of osteoarthritis 11 .…”
Section: Introductionmentioning
confidence: 99%